The junior secondary course of the Cape Province and the dull-normal child : (a pilot study based on research in the Border area and the North-Eastern districts) - Loots, Francois Jacobus (Rhodes University, Faculty of Education, Department of Education, 1960)
[Aims of Dissertation and Investigation, p. ix-x] The aim of this dissertation is to analyse and evaluate the results of the new junior secondary course in respect of the dull-normal child ... How well did the junior secondary course succeed in meeting the needs of the dull-normal child? That is the question which this investigation will attempt to answer.
Keywords: Education, Secondary -- South Africa -- Cape of Good Hope; Children -- Intelligence levels; Children with mental disabilities -- Education -- South Africa -- Cape of Good Hope